Microorganism mediated biosynthesis of metal chalcogenides; a powerful tool to transform toxic effluents into functional nanomaterials - Vena, María Paula (2015)
Cadmium contained in soil and water can be taken up by certain crops and aquatic organisms and accumulate in the food-chain, thus removal of Cd from mining or industrial effluents – i.e. Ni-Cd batteries, electroplating, pigments, fertilizers – becomes mandatory for human health. In parallel, there is an increased interest in the production of luminescent Q-dots for applications in bioimaging, sensors and electronic devices, even the present synthesis methods are economic and environmentally costly. An alternative green pathway for producing Metal chalcogenides (MC: CdS, CdSe, CdTe) nanocrystals is based on the metabolic activity of living organisms. Intracellular and extracellular biosynthesis of can be achieved within a biomimetic approach feeding living organisms with Cd precursors providing new routes for combining bioremediation with green routes for producing MC nanoparticles. In this mini-review we present the state-of-the-art of biosynthesis of MC nanoparticles with a critical discussion of parameters involved and protocols. Few existing examples of scaling-up are also discussed. A modular reactor based on microorganisms entrapped in biocompatible mineral matrices – already proven for bioremediation of dissolved dyes – is proposed for combining both Cd-depletion and MC nanoparticle's production.